2012
DOI: 10.1177/0265407512464483
|View full text |Cite
|
Sign up to set email alerts
|

A prototype analysis of relational boredom

Abstract: Boredom has been described as a major obstacle to maintaining lasting love (Aron & Aron (1986). However, empirical research on this important challenge to relationship maintenance has been hampered by the lack of an agreed-upon definition of the construct. We tested the hypothesis that relational boredom is amenable to a prototype conceptualization. In study 1, participants provided prototypicality ratings for the features of relational boredom. Features such as ''lack of interest in partner'' and ''no longer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Birnie-Porter and Lydon (2013) argue that a prototype analysis is warranted when researchers attempt to answer the question: "What is it?" and Harasymchuk and Fehr (2013) advocated for a prototype approach when there is lack of consensus on the definition of a concept. No simple infidelity definition exists because the concept cannot be classically defined in black and white terms.…”
Section: A Prototype Approach To Infidelitymentioning
confidence: 99%
See 1 more Smart Citation
“…Birnie-Porter and Lydon (2013) argue that a prototype analysis is warranted when researchers attempt to answer the question: "What is it?" and Harasymchuk and Fehr (2013) advocated for a prototype approach when there is lack of consensus on the definition of a concept. No simple infidelity definition exists because the concept cannot be classically defined in black and white terms.…”
Section: A Prototype Approach To Infidelitymentioning
confidence: 99%
“…It is possible that how an individual conceptualizes and understands infidelity may relate to the likelihood that they engage in this behavior. Second, a prototype approach allows researchers to understand the breadth of a concept (Gregg, Hart, Sedikides, & Kumashiro, 2008) and potentially highlight previously ignored components of the concept (Harasymchuk & Fehr, 2013). Lay theories of relationships shape individuals' relationship behaviors (Fletcher & Thomas, 1996), so further identifying the various components of these lay theories may again help us to better understand infidelity.…”
Section: Why Are Lay Conceptions Of Infidelity Important?mentioning
confidence: 99%
“…As mental toughness is typically measured through self-report scales that are developed from theoretical or sporting-based conceptualisations, it is important for researchers to understand how these tools correspond to participants' ideas of the concept. Second, as the meaning of mental toughness is likely to be contextually bound (Bull et al, 2005;Fawcett, 2011;Madrigal, Hamill, & Gill, 2013), lay theories may highlight previously overlooked components of mental toughness (Harasymchuk & Fehr, 2013). Finally, understanding lay perceptions of mental toughness may contribute to promoting further recognition and understanding of the benefits that can be attained by mental toughness beyond sporting and achievement-related contexts.…”
Section: [In Order Of Importance]mentioning
confidence: 99%
“…Studies have found that boredom predicts relationship dissatisfaction and break-down (Aron & Aron, 1996;Harasymchuk & Fehr, 2013;Tsapelas, Aron & Orbuch, 2009). In prototype analysis of relational boredom, Harasymchuk and Fehr (2013) found that a main feature of boredom in a romantic relationship was loss of positive qualities once experienced in the relationship (e.g., lack of excitement, passion, fun, and surprises).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%